PRAANGGAPAN DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Indah Irawani; Abdussamad Abdussamad; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractPresuppositions are initial assumptions before speaking to minimize the possibility of misunderstandings in giving and receiving information when communicating. The reason researchers are interested in researching Presuppositions of the novel About You by Tere Liye is because presuppositions can help interpret a speech between speakers and speech partners in the process of conveying information so that there is little chance of misunderstanding in communicating. The purpose of this studyis to describe the elements of prejudice understanding contained in the novel About You by Tere Liye, the types of presuppositions used in contained of the novel About You by Tere Liye and texts related to About You novel by Tere Liye in Indonesian language learning Class XII Curriculum. 2013.The method in this study is descriptive method. The approach in this research is a pragmatic approach. The source of this research data is the novel About You published by Gramedia Pustaka Utama with a total of 524pages.The data collection techniquesin this study are listening and recording.The data was analyzed using Yule's theory.The results showed that there were five types ofpresuppositions found from 39 data contained in the novel About You by TereLiye are 1 presumption of data non-active, 1 presupposition of data counterfactual, 12presupposition of datafactive, 12presupposition of data structural and 13 presupposition of data existential. Of the 39 data found, existential presuppositionis the most dominant type of presupposition in the novel About You by Tere Liye.Keywords: Presuppositions, Shared Knowledge, Participants, and The Context